Black cotton soil modification by the application of waste materials - Gupta C.; Sharma R.K. (My University, 2025)
The black cotton soil is a type of problematic expansive soil which causes many problems in the construction of structures founded on them. It is having a swelling and impervious nature with poor geotechnical subgrade characteristics. In this research an approach is made towards the way of improvement in the various geotechnical properties of black cotton soil such as index properties, swelling characteristics, consolidation characteristics, hydraulic conductivity characteristics and strength characteristics by blending it with waste materials such as river sand, fly ash and marble dust. Hence, from these approaches, the impacting effect of waste materials on the environment reduced due to optimum utilization of these waste materials in the improvement in various properties of black cotton soil. © 2016, Technical University of Budapest. All rights reserved.